Omeprazole prescriptions for older adults in health care units in Curitiba, Brazil: an analysis based on Beers Criteria - Juliana Sambugaro; Hudson Prestes dos Santos; Linda Tieko Kakitani Morishita; Alexandra Ingrid dos Santos Czepula (Brazilian Society of Geriatrics and Gerontology, 2021)
OBJECTIVE: To evaluate omeprazole prescriptions for older adults based on the Beers Criteria, with an analysis of indications and duration of use longer than eight weeks. METHODS: In this retrospective cross-sectional study, data were collected from the electronic medical records of older adults with an omeprazole prescription seen at two health care units in Curitiba, Brazil, between June and August 2019. Data were subjected to descriptive statistical analysis, Student t and χ2 tests. RESULTS: Medical records of 386 patients were analyzed, and 69.95% were female. The mean age was 71 (SD, 8.15) years. Most patients had incomplete primary education (50.52%) and income level ranging from one to two Brazilian minimum monthly wages (39.90%). No indication for omeprazole prescription was found in 23.83% of medical records. Use longer than eight weeks was predominant for all indications in 96.60% of medical records. Duration of use more extended than the Beers Criteria recommendation was independent of sex (p = 0.327), education (p = 0.805), and income level (p = 0.629). A relationship between polypharmacy and long-term drug use was demonstrated (p < 0.001). CONCLUSION: The results of this study suggest the need for periodic review of omeprazole prescriptions considering deprescribing when they appropriate.